A custom musculoskeletal model for estimation of medial and lateral tibiofemoral contact forces during tasks with high knee and hip flexions. Issue 10 (26th July 2020) - Bedo, Bruno Luiz Souza; Catelli, Danilo S.; Lamontagne, Mario; Santiago, Paulo Roberto Pereira
Abstract: Most of musculoskeletal models (MSKM) estimate the tibiofemoral joint reaction load at a single point or do not support large lower-limb ranges. This study aimed to adapt a generic MSKM that allows large knee and hip flexions to compute medial and lateral tibiofemoral contact forces (TFCF) during gait and squat tasks. The updated model includes medial and lateral knee compartment geometries that allow computing the vertical TFCF. The updated MSKM does not affect kinematics and kinetics outputs in both of the tasks, and the sum of the medial and lateral TFCF was equivalent to the net TFCF of the original MSKM.